How Cultural Value Can Influence The Nurse’s OCB in South Sulawesi - Andi Indahwaty Sidin; Nur Arifah; Ery Iswary; Ummu Kalsum (Universitas Aisyah Pringsewu, 2023)
Cultural value is a key factor in employee behavior in the workplace. Organizational Citizenship Behaviour (OCB) levels displayed will differ in different cultures. So this study aims to examine the effect of the cultural value dimensions of nurses on the Bugis, Makassar, Toraja, and Mandar tribes on Organizational Citizenship Behavior in hospitals. This research is quantitative research with a cross-sectional study approach to 500 respondents in 5 hospitals that are considered to represent the Bugis, Makassar, Toraja, and Mandar tribes. The sample was selected by simple random sampling, then analyzed using the Multiple Logistics Regression test on SPSS software. The results showed that cultural value was a predictor of OCB (0.000 less than 0.05), the power distance dimension showed the greatest influence on OCB with a p-value less than 0.05. Simultaneously, the cultural values of the Bugis, Makassar, Toraja, and Mandar tribes have a relationship with the OCB of nurses. This relationship shows that the higher the cultural values a nurse possesses, the higher the OCB displayed. In addition, it is known that the dimensions that significantly affect nurses' OCB are the power distance dimension. Therefore, the hospital management needs to pay attention to the influence of cultural values so that nurses’ extra-role performance can be maintained and improved. Abstrak: Nilai budaya merupakan faktor kunci dalam perilaku karyawan di tempat kerja. Tingkat Perilaku Kewarganegaraan Organisasi (OCB) yang ditampilkan akan berbeda dalam budaya yang berbeda. Sehingga penelitian ini bertujuan untuk menguji pengaruh dimensi nilai budaya perawat suku Bugis, Makassar, Toraja, dan Mandar terhadap Organizational Citizenship Behavior di rumah sakit. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross-sectional study terhadap 500 responden di 5 rumah sakit yang dianggap mewakili suku Bugis, Ma-kassar, Toraja, dan Mandar. Sampel dipilih dengan simple random sampling, kemudian dianalisis menggunakan uji Regresi Logistik Berganda pada software SPSS. Hasil penelitian menunjukkan bahwa nilai budaya merupakan prediktor OCB (0,000 kurang dari 0,05), dimensi power distance menunjukkan pengaruh terbesar terhadap OCB dengan p-value kurang dari 0,05. Secara bersamaan, nilai budaya suku Bugis, Makassar, Toraja, dan Mandar memiliki keterkaitan dengan OCB perawat. Hubungan tersebut menunjukkan bahwa semakin tinggi nilai budaya yang dimiliki oleh seorang perawat maka semakin tinggi pula OCB yang ditampilkan. Selain itu diketahui bahwa dimensi yang berpengaruh signifikan terhadap OCB perawat adalah dimensi power distance. Oleh karena itu pihak manajemen rumah sakit perlu memperhatikan pengaruh nilai-nilai budaya agar kinerja extra role perawat dapat dipertahankan dan ditingkatkan.